Enhanced carbon dioxide capture performance of natural mineral vermiculite‐derived lithium silicate with Na doping. Issue 2 (11th April 2022) - Wan, Yinji; Liu, Ying; Sun, Ruobing; Du, Yuntian; Xie, Mengkai; Qian, Gang; Liu, Zhisong; Liu, Minmin; Dan, Jianming; Yu, Feng
Abstract: Natural clay mineral‐derived functional materials have attracted considerable attention worldwide. Herein, natural mineral vermiculite (VMT)‐derived lithium silicate (VMT‐based Li4 SiO4 ) materials with different molar ratios of Na to Si were prepared for the high‐temperature CO2 capture. Among developed adsorbents, the VMT‐Li4 SiO4 ‐2Na materials displayed superior CO2 adsorption ability with 0.28 g/gadsorbent adsorption rate after 5 min and 33.67 wt% capture capacity at 650°C. The experimental investigations uncovered the presence of Li3 NaSiO4 or/and eutectic Li2 CO3 ‐Na2 CO3 molten salt resulting from the introduction of Na2 CO3, which resulted in higher CO2 uptake. Furthermore, the cyclic carbonation–decarbonation experiment of VMT‐Li4 SiO4 ‐2Na showed better stability when the O2 was used to perform the decarbonation step. We believe that the Na modified‐VMT‐based Li4 SiO4 adsorbent shows potential for practical applications in peak carbon dioxide emissions and carbon neutralization. © 2022 Society of Chemical Industry and John Wiley & Sons, Ltd.